ANALISIS NILAI-NILAI EFIKASI DIRI SANTRI DALAM BUKU AIR MATA SANTRI DI NEGERI PESANTREN KARYA NISA’ATUN NAFISAH - kulsum, Ummu; Arini, Aida; Ridhwan, Burhanuddin (EL-Islam, 2025)
Abstrack : The value of self-efficacy provides resilience and strength for students in facing difficult situations in Islamic boarding schools. An attitude of not getting bored easily, never giving up and several activities are characteristics of students have high self-efficacy. Students high self-efficacy are believed to be capable and capable of mastering various learning tasks, and are able to regulate their own learning methods so that success in academic and non-academic fields is very possible to achieve. The focus of this research is: 1) What are the self-efficacy values of santri in the book Air Mata Santri Di Negeri Pesantren by Nisa'atun Nafisah, 2) What are the results of self-efficacy of santri in the book Air Mata Santri di Negeri Pesantren. This research method uses library research, qualitative descriptive in nature. The data source that the researcher used was primary data source obtained from the works of Nisa'atun Nafisah. Secondary data sources were obtained from other books that discuss the research in this thesis. Data collection method, researchers use the documentation method. The researcher's data analysis method uses deductive methods and inductive methods. Based on the results of the analysis that has been carried out in the book Air Mata Santri Karya Nisa'atun Nafisah, it can be concluded that there are efficacy values in the book Air Mata Santri Nisa'atun Nafisah, namely values (1) independent, (2) Independent, (3) ) hard work, (4) love of the country, (5) responsibility, (6) discipline, (7) love of peace, (8) social care, (9) communicative, and (10) creativity.